Zróżnicowanie siedlisk i drzewostanów w lasach gminy Szadek - Woziwoda, Beata (Biuletyn Szadkowski, 2009)
The forests of Szadek commune are diversify with regard to habitat conditions and tree stand composition. Over a century of use of the forests as a result of the fragmentation of forests complexes, exploitation of the forest for timber, cultivation of Pinus sylvestris monocultures, introduction of alien wood species (Quercus rubra, Robinia pseudoaccacia) and a change of water regime and soil conditions, the natural forests have been changed and new anthropogenic communities have been developed. The present structure and species composition of tree stand are mainly a result of forest management and frequently they are incompatible with habitat conditions.